INFORMATION TECHNOLOGY IN SURVEILLANCE OF EMPLOYEE PERFORMANCE - Mrs. Karthika Vinith, Mr. Denzil Edrod Pinto, (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
This research paper examines the role of Information Technology in monitoring employee performance in companies. Organizations use performance management software that helps employee performance through key performance indicators, goal setting and performance reviews. It identifies the aids, issues, and effects of employing IT-based monitoring systems to identify employee lexical efficiency. Through the literature review, this study explores the technologies utilized in monitoring employee performance and outlines the research approach, encompassing case studies, surveys, interviews with HR professionals and employees. The result approaches that IT-based performance monitoring can steer organizational translucency, simplify input mechanisms along with concerns related to data privacy, employee morale, and potential ethical issues. Organizations makes use of time and attendance systems to track employee hours worked and absences which helps in monitoring employee punctuality, attendance patterns, and compliance to work schedules. The discussion makes an impact in fostering a performance-oriented culture and employee engagement, while acknowledging the need for clear communication and transparent policies. In conclusion, this research paper highlights that while IT offers invaluable tools to monitor employee performance, a balanced approach is essential to ensure both organizational efficiency and employee well-being. Organizations must carefully consider the ethical and privacy implications of using IT-based systems and prioritize employee involvement in decision-making processes to create a positive and productive work environment.